Dislocation Creep of Olivine: Backstress Evolution Controls Transient Creep at High Temperatures. Issue 5 (17th May 2021) - Hansen, Lars N.; Wallis, David; Breithaupt, Thomas; Thom, Christopher A.; Kempton, Imogen
Abstract: Transient creep occurs during geodynamic processes that impose stress changes on rocks at high temperatures. The transient is manifested as evolution in the viscosity of the rocks until steady‐state flow is achieved. Although several phenomenological models of transient creep in rocks have been proposed, the dominant microphysical processes that control such behavior remain poorly constrained. To identify the intragranular processes that contribute to transient creep of olivine, we performed stress‐reduction tests on single crystals of olivine at temperatures of 1, 250°C–1, 300°C. In these experiments, samples undergo time‐dependent reverse strain after the stress reduction. The magnitude of reverse strain is ∼10 −3 and increases with increasing magnitude of the stress reduction. High‐angular resolution electron backscatter diffraction analyses of deformed material reveal lattice curvature and heterogeneous stresses associated with the dominant slip system. The mechanical and microstructural data are consistent with transient creep of the single crystals arising from accumulation and release of backstresses among dislocations. These results allow the dislocation‐glide component of creep at high temperatures to be isolated, and we use these data to calibrate a flow law for olivine to describe the glide component of creep over a wide temperature range. We argue that this flow law can be used to estimate both transient creep and steady‐state viscosities of olivine, with the transient evolution controlled by the evolution of the backstress. This model is able to predict variability in the style of transient (normal vs. inverse) and the load‐relaxation response observed in previous work. Plain Language Summary: At high temperatures and over long timescales, rocks can flow in a similar manner to viscous fluids. If the stresses in Earth that drive the flow of rocks change suddenly in magnitude (e.g., after an earthquake), the viscosity of the rock changes and evolves. This evolution in viscosity influences how quickly the stress is relaxed or starts to build up again. We do not currently understand the underlying physics controlling this evolution in viscosity, which reduces our ability to predict and evaluate many aspects of flow in Earth's interior. Key Points: Stress‐reduction experiments reveal that transient creep of olivine is controlled by dislocation interactions Equations describing deformation due to glide of dislocations and the buildup of backstress are applicable at low and high temperatures Our proposed framework for dislocation creep allows prediction of yield stresses, strain hardening, transient creep, and load relaxation